Isolation, characterization and antimicrobial assay of some compounds from Sarcophyton tortuosum - Penalosa, Beatriz Agustin (Animo Repository, 1991)
The chloroform extract of the marine soft coral Sarcophyton tortuosom was found to contain two compounds with potent antimicrobial properties. The structures of the two compounds were partially elucidated. Based on the spectral evidences (IR, 1H NMR, 13C NMR) and comparison of its 13C chemical shifts with those of sitosterol the structure of ST7/2 was proposed as a steroid, possessing a 3 Beta-hydroxy-delta5 steroid nucleus. The structure of its side chain could not be determined. Analysis of the spectral data of ST4/4 suggested that it was a triglyceride with a cyclopropene ring in the side chain. Both compounds inhibited the growth of all seven test organisms but exhibited their highest inhibitory effect on Bacillus subtilis.